Evaluation of elite lines of cowpea (Vigna unguiculata (L.) Walp.) for leaf/fodder plus grain (i.e., dual purpose) - Akundabweni, L.S.; Peter-Paul, C.; Singh, B.B. (1990)
The line TVx1948-01F gave the best combination of high grain yield and high yield of fresh leaves for human consumption and fodder. Generally, lower total fresh leaf yields were associated with early to medium flowering and high total pod and total grain yields.